Synthesis and characterization of (S)-5-(2-Methylbutoxy)-2-[[[4-Hexylphenyl]Imino]Methyl]Phenol liquid crystal by inverse gas chromatography - Ocak, H.; Yazici, O.; Eran, B. Bilgin; Cankurtaran, O.; Karaman, F. (NATL INST OPTOELECTRONICS, 2008)
Liquid crystalline compound (S)-5-(2-methyl butoxy)-2-[[[4-hexyl phenyl]imino]methyl]-phenol (MBHPIMP) has been prepared and characterized. Phase transition temperatures of MBHPIMP were determined by polarizing microscopy, differential scanning calorimetry and inverse gas chromatography. Trace amount of solvents such as methyl acetate, ethyl acetate, pentane, hexane, cyclopentane, cyclohexane were passed through the gas chromatography column loaded with MBHPIMP coated on Chromosorb W. MBHPIMP exhibits liquid crystal properties with calamitic molecular shape which has a chiral moiety and alkyl chain at the terminus. The retention diagrams of the solvents on the liquid crystal were plotted by means of specific retention volumes, V-g(0) at the temperatures in degrees C between 40 and 95 by inverse gas chromatography. The weight fraction activity coefficient, Q(1)(infinity), Flory-Huggins liquid crystal-solvent interaction parameter, chi(infinity)(12), equation of state liquid crystal-solvent interaction parameter, chi*(12) and effective exchange energy parameter, chi(infinity)(12), related to the MBHPIMP-solvent systems were obtained. In addition, the partial molar heats of sorption, Delta(H) over bar (1,sorp) and mixing, Delta(H) over bar (infinity)(1)were determined.
Keywords: liquid crystals; salicylaldimine; inverse gas chromatography; phase transition temperature; interaction parameter; THERMODYNAMICS; COMPLEXES; POLYMER; Materials Science; Optics